Job satisfaction, effort, and performance: A reasoned action perspective - Icek Ajzen (Contemporary Economics, 2011)
In this article the author takes issue with the recurrent reliance on job satisfaction to explain job-related effort and performance. The disappointing findings in this tradition are explained by lack of compatibility between job satisfaction - a very broad attitude - and the more specific effort and performance criteria. Moreover, attempts to apply the expectancy-value model of attitude to explore the determinants of effort and performance suffer from reliance on unrepresentative sets of beliefs about the likely consequences of these behaviors. The theory of planned behavior (Ajzen, 1991, 2012), with its emphasis on the proximal antecedents of job effort and performance, is offered as an alternative. According to the theory, intentions to exert effort and to attain a certain performance level are determined by attitudes, subjective norms, and perceptions of control in relation to these behaviors; and these variables, in turn, are a function of readily accessible beliefs about the likely outcomes of effort and performance, about the normative expectations of important others, and about factors that facilitate or hinder effective performance.
Keywords: A12; 330; job satisfaction; job performance; expectancy-value model; theory of planned behavior